2011
DOI: 10.1108/14013381111197234
|View full text |Cite
|
Sign up to set email alerts
|

Conflicting conceptualizations of human resource accounting

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…Furthermore, numerous other studies show that human capital reporting is relatively weak in the UK (Bassi et al, 2015;Li et al, 2008;Steen et al, 2011;Striukova et al, 2008). Critics of the UK system report that following the Second World War, the reason why British organizations have lower human capital reporting quality is because the UK has moved away from a philosophy of being employee focused to be controlled by private equity holders (Metcalf, 1989;Nolan, 2011Nolan, , 2012.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, numerous other studies show that human capital reporting is relatively weak in the UK (Bassi et al, 2015;Li et al, 2008;Steen et al, 2011;Striukova et al, 2008). Critics of the UK system report that following the Second World War, the reason why British organizations have lower human capital reporting quality is because the UK has moved away from a philosophy of being employee focused to be controlled by private equity holders (Metcalf, 1989;Nolan, 2011Nolan, , 2012.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second, South Korea and the UK have different philosophical outlooks on human capital. The UK is recognized as having lower levels of human capital information compared to many other developed economies (Bassi et al, 2015;Fincham and Roslender, 2003;Li et al, 2008;Roslender and Stevenson, 2009;Steen et al, 2011;Striukova et al, 2008;Vandemaele, et al, 2005). A potential reason why human capital information is not robust in the UK is because following the Second World War, shareholder profit has superseded employees' wellbeing as an organizational strategy (Koumenta and Williams, 2019;Metcalf, 1989;Nolan, 1989Nolan, , 2012.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…In general, non-financial reporting complements or rather supplements financial understanding and it is assumed that intellectual capital fulfils the gap in between Market Value (MV) and Booked Value (BV). Bukh, Larsen and Mouritsen (2001) severely criticise the argument, however due to increase subjectivity in human capital valuation it is difficult to construct and capture, and also criticise, the exact value of human resources employed at work (Steen, Welch & McCormack, 2011). Data reported is dry and only indirectly connected like sick leave days, employee turnover, which are rather effects of burnout.…”
Section: Academic Perspectives: Human Resources Accountingmentioning
confidence: 99%
“…Resources can be either tangible or intangible assets and capabilities are the ability to exploit and combine resources effectively [48]. The human resource capabilities of an organization are commonly accepted to be suitable for RBV research [49,50], and many of its activities can be central to the core competencies of an organization [51]. Within the context of this study, it is suggested that employee management and development is unique to each organization and as such, is considered as a competency that may be leveraged to enable the competitive edge.…”
Section: Theoretical Perspective Of the Resource-based Viewmentioning
confidence: 99%